SUMBER DAYA INTERNAL PETERNAK SAPI PERAH DAN PENGARUHNYA TERHADAP DINAMIKA KELOMPOK DAN KONTEKS KERENTANAN - Amam Amam; M. Wildan Jadmiko; Pradiptya Ayu Harsita; Nur Widodo; M. Setyo Poerwoko (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
This research aims to find out the influence of dairy farmer’s internal resources on group dynamics and vulnerability context of dairy farming business. The research was conducted at the animal husbandry institution Kelompok Usaha Bersama (KUB) Tirtasari Kresna Gemilang in Pujon Subdistrict, Malang District, East Java Province on October - December 2018. The research variables consisted of financial resources (X1), technological resources (X2), physical resources (X3), group dynamics (Z1), and the context of vulnerability of dairy farming business (Y1). The respondents were all KUB member dairy farmers, namely 174 dairy farmers. Data were analyzed by the SEM (Structural Equation Model) method using SmartPLS 2.0. The results showed that the accessibility of dairy farmers to internal resources affected group dynamics by 33%, while vulnerability context of dairy farming business was influenced by the dairy farmer’s internal resources and group dynamics by 30.3%. The conclusion of the research showed the role of resources could influence to group dynamics and vulnerability context of dairy farming business. Keywords: Dairy Cattle, Farming Business, Group Dynamics, Internal Resources, Vulnerability Context